The Analysis and the Optimizat ion of an Auto nomous Mobile Plat form Equipped with a Manipulator Arm for Sample Retrieval in Rough Terrain - A.M. Țîțu; D. Bâlc; M. Nabiałek; M.L. Rozemarie; E. Bâlc (Archives of Metallurgy and Materials, 2025)
The current study delves into a detailed analysis and optimization of an autonomous mobile platform, meticulously designed to navigate, and operate within the complexities of rough and challenging terrains. This platform isn’t just an ordinary machinery; it’s equipped with a manipulator arm, strategically designed to facilitate smooth sample retrieval, even in the most rugged environments. The autonomous mobile platform is suitable even for remote and hostile terrain, inaccessible to most conventional means of exploration. With a robust design and advanced capabilities, it’s crafted to navigate through obstacles effortlessly, ensuring that no potential sample remains uncollected. But the autonomous mobile platform doesn’t stop there, as it’s further distinguished by the integration of communication technology, which elevates its functionality to a whole new level. Real-time data transmission is one of the defining features of the platform. It allows for the continuous flow of information between the platform and its operators, facilitating swift decision-making and seamless coordination. This real-time data transmission isn’t limited to basic telemetry but encompasses a wide range of sensor data, providing valuable insights into the surrounding environment and the platform’s status itself. But perhaps one of the most revolutionary aspects of this platform is its ability to stream live video feeds to its operators. The opportunity to witness the sample retrieval process unfold in real-time, from the comfort of a remote command center, can be one of the advantages offered by the autonomous mobile platform. This live video streaming feature isn’t just a luxury; it’s a gamechanger. It provides operators with a visual perspective that surpasses mere data points, enabling more informed decision-making and better situational awareness. Additionally, the manipulator arm of the platform isn’t just a passive tool; it’s a versatile asset that significantly extends its capabilities. With a range of motion and precision that rivals even the most skilled human operators, the manipulator arm ensures that samples can be retrieved from almost any location, regardless of accessibility or terrain. Whether it’s collecting geological samples from a steep slope or extracting soil samples from beneath the surface, the manipulator arm gets the job done with unmatched efficiency and precision.